2015
DOI: 10.1093/infdis/jiv263
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Asymptomatic Respiratory Syncytial Virus Infections During an Epidemic in a Rural Kenyan Household Cohort

Abstract: Background. The characteristics, determinants, and potential contribution to transmission of asymptomatic cases of respiratory syncytial virus (RSV) infection have not been well described.Methods. A cohort of 47 households (493 individuals) in coastal Kenya was recruited and followed for a 26-week period spanning a complete RSV season. Nasopharyngeal swab specimens were requested weekly, during the first 4 weeks, and twice weekly thereafter from all household members, regardless of illness status. The samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 32 publications
3
68
0
Order By: Relevance
“…Last, we collected weekly specimens and our findings may be biased if non-infant younger children had longer shedding duration compared to older children. However, this has not been demonstrated in studies of RSV and HRV shedding duration [28,30]. Our large cohort allowed us to use a multivariable analysis to identify the risk factors and protective characteristics associated with the incidence of transmission.…”
Section: Epidemiology and Infectionmentioning
confidence: 93%
“…Last, we collected weekly specimens and our findings may be biased if non-infant younger children had longer shedding duration compared to older children. However, this has not been demonstrated in studies of RSV and HRV shedding duration [28,30]. Our large cohort allowed us to use a multivariable analysis to identify the risk factors and protective characteristics associated with the incidence of transmission.…”
Section: Epidemiology and Infectionmentioning
confidence: 93%
“…It is possible that these respiratory viruses are transient, colonizing the patients' upper respiratory tract but not actually causing the symptoms or disease. However, although asymptomatic infections due to adenovirus and PIV are often found in children [11,27,28], adenovirus and PIV are rarely detected among healthy asymptomatic adults [11,29].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Second, the fever/RS group and non-fever/RS group were matched for age and sex. The matching of age is particularly important because previous studies have shown that the proportion of patients with symptoms varies according to age [28]. Another unique feature in this study is that we have included patients with fever but without respiratory symptoms in the fever/RS group because many clinicians test respiratory viruses in febrile patients without respiratory symptoms.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The intensive surveillance provided detailed infection data that allowed comprehensive investigation of the circulation of the respiratory viruses in the community. Previous reports have described the data on respiratory syncytial virus (RSV) in detail [4][5][6][7], and here we present data on a wide range of respiratory viruses. and Demographic Surveillance System [8].…”
mentioning
confidence: 93%
“…The study period spanned from 8 December 2009 to 5 June 2010. The study design and the details of field operations have been previously described [4][5][6][7]. Identifying who infects the infant with RSV in the household was the primary objective of the study [6].…”
mentioning
confidence: 99%